Variations in biological attributes and phenolics of enzymatically hydrolysed medicinal plant extracts (Bangladesh Journal of Botany, 2020)
Major objective of this study was to appraise the variations in biological activities and phenolics of enzymatically hydrolysed medicinal plants, namely Morus alba (L.), Momordica balsamina (L.), Capparis spinosa (L.), Pongamia pinnata (L.) and Peganum hermala (L.) indigenous to Pothoharic region of Pakistan. Enzyme cocktails such as kemzyme dry-plus, natuzyme and zympex-014 were employed for enzyme-assisted extraction. Best antimicrobial activity was exhibited by zympex-014 produced extracts against selected strains of bacteria and fungi with inhibition zone of 18.54 and 21.45 mm, respectively. Similarly, zympex- 014 produced C. spinosa extract (1.21%) exhibited least hemolytic activity. However, greater thrombolytic activity (51.93%) was exhibited by kemzyme dry-plus produced M. balsamina extract. Moreover, major phenolics detected in selected medicinal plants using RP-HPLC were gallic acid (272 μg/g), quercitin (269 μg/g), benzoic acid (184 μg/g), vanillic acid (100 μg/g) and cinnamic acid (68 μg/g). Overall, the above results revealed that enzymatic pre-treatment facilitated in the liberation of bound phenolic moieties from selected medicinal plants and thus improved their biological attributes.